PENGARUH ANGGARAN BIAYA OPERASIONAL TERHADAP EFISIENSI BIAYA OPERASIONAL PADA PT PELABUHAN INDONESIA I CABANG BELAWAN - Bayu Pratama; Kiki Farida; Yohny Anwar (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
This study aims to provide a look at the Effect of Operational Cost Budget on Operational Cost Efficiency. The population used in this study is the income statement at PT Pelabuhan Indonesia 1 Belawan Branch, the sample in this study is the company's budget and its realization during a certain period. The data analysis techniques used in this research are Simple Linear Regression Analysis, Classical Assumption Test (Normality Test, Multicollinearity Test, Heteroscedasticity Test, and Autocrelation Test) and Hypothesis Testing (R2 Test, and t-Test). This research uses SPSS 21 software to process the existing data. The results of this study partially show that the Operational Cost Budget has a significant effect on the Operational Cost.Keywords : Operational Cost Budget, Operating Costs.